Estudo fitoquímico e da atividade biológica de óleos essenciais, extratos e constituintes de Magonia pubescens A.St.-Hil. (Sapindaceae) - Acácio Raphael Aguiar Moraes (2021)
Magonia pubescens is a natural species from the Brazilian cerrado which are employed in traditional medicine. For example, the trunk bark is used to produce homemade soaps to treat seborrhea and skin problems. Moreover, its roots are popularly used in a traditionally indigenous practice called “tingujar”, the source of its the popular name “tinguí”. This work describes the study of the chemical composition of inflorescences, roots and branches of M. pubescens through the use of chromatographic techniques, UV absorption spectroscopy, mass spectrometry and nuclear magnetic resonance spectroscopy. The essential oil from M. pubescens inflorescences was studied for the first time, and the effect of gamma radiation on its chemical integrity was evaluated at different radiation doses. In this oil, 14 components were identified, belonging to the classes of monoterpenes, sesquiterpenes and fatty acids. All essential oils obtained from plant material non-irradiated or irradiated, with doses of 1, 3, 5 or 10 kGy showed cytotoxic activity against myeloid leukemia K562 and human breast adenocarcinoma MDA-MB-435 strains. Non-irradiated material provided the most active oil (OE0) against K562 cells (IC50 22.10 ± 1.98 µg/mL), whereas the 3 kGy irradiated material furnished the most effective oil (OE3) against MDA-MB-231 (IC50 29.05 ± 2.70 µg/mL. However, no significant changes were observed for the cytotoxic activity of the oils between radiated and non-irradiated materials. The phytochemical study of the ethanolic extract of the roots yielded seven secondary metabolites (scopoletin, stigmasterol, eriodictyol, cleomiscosin A, lophirone A, proanthocyanidine A2 and mellein), all identified for the first time in this species. Furthermore, a biomonitored study was carried out with the ethanolic extract to obtain fractions with antiparasitic activities. Fractions were identified with amebicidal (IC50 15.91 - 67.15 g/mL against Naeglari fowleri), leishmanicidal (IC50 5.99 – 24.95 g/mL) and trypanocidal (IC50 22.11 – 51.15 µg/mL). Finally, the classical phytochemical study of the hexanic and dichloromethanic extracts from the branches led to the isolation lapachol, stigmasterol, maniladiol and scopoletin, all identified for the first time in this species. Fifty-three compounds were also identified through UHPLC-HRMS analysis of partitioned aqueous extracts from branches, including cumarins, flavonoids, terpenes and saponins. In addition, the cytotoxicity analysis of these aqueous extracts established biologically active fractions (IC50 32.68 µg/mL for THP-1, IC50 40.85 µg/mL for K562 and IC50 75.12 µg/mL for MDA-MB- 231).